Travelling with Father Morin: Missionaries, colonial projects, and the transnational core of national debates in Quebec (Canada Watch, 2018)
Tracing his writings and reflections can help us understand the historical roots of Quebec’s understanding of Islam and non-Western  cultures more broadly.